The factors affecting dependency on smartphone behaviour towards selected millennials in Johor Bahru / Siti Munirah Abd Kadir - Abd Kadir, Siti Munirah (Faculty of Business and Management, 2018)
During the last decade, smartphone has gained popularity around the world. Smartphone technology can be characterized as a multi-function device that helps people to manage their task. Despite a huge spike in smartphone use, the Generation Y or the Millennials ordinarily are negligent of the consecution being too dependent on smartphones. Consequently, this study ought to investigate the factors affecting dependency on smartphone behavior towards selected Millennials in Johor Bahru. This study reviewed several theories of anxiety, obsession, social withdrawal, and reliance as possible factors affecting dependency on smartphone behavior towards selected Millennials in Johor Bahru. A convenience sampling technique was used to select a sample of 384 respondents from target population of 536,900 Millennials in Johor Bahru. Data analysis was carried out using quantitative technique with the aid of Statistical Package for Social Science (SPSS). Pursuant to the findings, it was discovered that all four independent variables; anxiety, obsession, social withdrawal, and reliance have shown positive association with dependency on smartphone.